The Importance of the Actual Recognition Of Biological Assets in the Financial Statements - Pérez Méndez, Paola Fabiola
The objetive of this research article is to explain the importance of the real recognition of biological assets within the operation of entities whose economic activity is related to agricultural activities, arguing its relevance and viability, reasons that can be visualized and expanded to each of the processes of the accounting and financial area, mentioning the position of several authors who have researched on the subject and how these findings can be found they can build their own, precise, effective knowledge, with an eminent social impact, applicable to the processes of the entity under study, the methodology used in The research is applied, with a quantitative and qualitative approach; With a non-experimental descriptive and field design, it is aimed at identifying and obtaining the necessary information to recognize and measure the biological assets existing in the Gaira Aquaculture Center (CAAG), generating a positive impact on the biological. quantitatively and qualitatively in the information that becomes input in decision-making, it should be noted that this article is the product of the execution of the research project called: "Recognition and measurement of biological assets as a source of added value in financial statements", approved in the internal call Sennova (Research, Innovation and Technological Development System of the National Learning Service) 2022.